Chatbots as Peer Counselors in Helping DLSU Senior High School Students Manage Their Stress: Socio-Technical Requirements - Pena, Franco Gabriel M. (Animo Repository, 2023)
Pressure to perform well academically and relationships with family and friends cause varying degrees of stress among students that can affect the functionality and stability of their mental health. One of the known solutions in reducing stress is peer counseling where experiences and hardships are shared with trusted peers in order to receive support from one another. Peer counseling has benefitted the support seeker and the support providers who are involved in the peer counseling session. The advancement of technology has made significant development in the application of accessible technologies in healthcare, including mental health. The use of chatbots has been recently introduced as well as its potential in serving as an alternative platform to help individuals cope with stress and manage their well-being. In this study, senior high school students of De La Salle University were interviewed to identify the causes of their stress, to determine the strategies they employ in managing their stress with particular emphasis on peer counseling, and to solicit feedback on their perception in using a chatbot as a peer counselor. Findings from this study may provide insights on the ideal characteristics of a chatbot as a peer counselor that can inform future designers of such technologies to support stress management.